Komunikasi Partisipatif dan Jaringan Komunikasi dalam Membangun Aksi Kolektif Perkumpulan Petani Pengguna Air (P3A) di Daerah Irigasi Papah - Rizki Mila Amalia; Sarwititi Sarwoprasodjo; Resfa Fitri (Jurnal Komunikasi Pembangunan, 2017)
The research background is government’s goal to achieve food self-sufficiency, but it is difficult to increase food production because of the water scarcity due to climatic anomalies, presumably may affect communication activities and collective action of groups that manages irrigation system at the grassroots level. The objectives of this research are to analyze the level of participatory communication and communication network in group, and also to analyze its impact to collective action rates. Research was conducted on Farmer Water Users Associations in irrigation area Papah, began in March to April 2016. The approach taken with qualitative method and designed as a census on the character of descriptive correlation. The result showed that good ability on dialogue and high chance of expressed aspirations, did not necessarily made the participation of members in collective action becomes high. Collective action find in P3A with difficulty in obtaining water for their farming activities in the dry season. Network density GP3A Papah is 1,4 percent, it means low interaction occurs among actors. Collective action would decrease in P3A with high-density network, because in these conditions would create a closed network and occurred high homogeneity of the information so new informations and innovations difficult to enter the network.Keywords : aspiration, collective action, communication network, dialogue